Non‐linear optimal control for multi‐DOF electro‐hydraulic robotic manipulators. Issue 2 (1st June 2020) - Rigatos, Gerasimos; Zervos, Nikolaos; Abbaszadeh, Masoud; Pomares, Jorge; Wira, Patrice
Abstract : A non‐linear optimal (H‐infinity) control approach is proposed for the dynamic model of multi‐degree‐of‐freedom (DOF) electro‐hydraulic robotic manipulators. Control of electro‐hydraulic manipulators is a non‐trivial problem because of their non‐linear and multi‐variable dynamics. In this study, the considered robotic system consists of a multi‐link robotic manipulator that receives actuation from rotary electro‐hydraulic drives. The article's approach relies first on approximate linearisation of the state‐space model of the electro‐hydraulic manipulator, according to first‐order Taylor series expansion and the computation of the related Jacobian matrices. For the approximately linearised model of the manipulator, a stabilising H‐infinity feedback controller is designed. To compute the controller's gains, an algebraic Riccati equation is solved at each time‐step of the control algorithm. The global stability properties of the control scheme are proven through Lyapunov analysis. The proposed control method retains the advantages of typical optimal control, i.e. fast and accurate tracking of the reference setpoints under moderate variations of the control inputs.